If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -2) + x = 10(x + -2) + 2 Reorder the terms: 9(-2 + x) + x = 10(x + -2) + 2 (-2 * 9 + x * 9) + x = 10(x + -2) + 2 (-18 + 9x) + x = 10(x + -2) + 2 Combine like terms: 9x + x = 10x -18 + 10x = 10(x + -2) + 2 Reorder the terms: -18 + 10x = 10(-2 + x) + 2 -18 + 10x = (-2 * 10 + x * 10) + 2 -18 + 10x = (-20 + 10x) + 2 Reorder the terms: -18 + 10x = -20 + 2 + 10x Combine like terms: -20 + 2 = -18 -18 + 10x = -18 + 10x Add '18' to each side of the equation. -18 + 18 + 10x = -18 + 18 + 10x Combine like terms: -18 + 18 = 0 0 + 10x = -18 + 18 + 10x 10x = -18 + 18 + 10x Combine like terms: -18 + 18 = 0 10x = 0 + 10x 10x = 10x Add '-10x' to each side of the equation. 10x + -10x = 10x + -10x Combine like terms: 10x + -10x = 0 0 = 10x + -10x Combine like terms: 10x + -10x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| (-6i)(-6i)=0 | | 28x^2-13x-6=0 | | 1/4+1/3-4/5 | | 10(-0.55)-7y=96.9 | | 25z^2-4y^2=0 | | 1/4+1/3-4/4 | | 8-x=3x-4 | | 2x-3/8+x=2x+3/2+4 | | (-1+6i)+(-4+2i)=0 | | -x-7=3x+5 | | 49x^2-169=0 | | 4(x-3)-(2x-5)=2 | | 19-5x=6-10x | | 10x-7(3.1)=67.7 | | x(9-x)=0 | | 3m/6m | | 4a+2b-3=5 | | 11/3+21/3 | | 5-3(a-1)=4+a | | 2t/3=15 | | 4(2x-1)=3-(2x+2) | | -3(x+5)-3=-18 | | 4x-2/8+x=4x+2/4+1 | | 4x+14=63-3 | | x-3/6+x+4/5=7/6 | | 80-2r=-2 | | 1.3(8-x)=1.1(6-x) | | 4a^2+25=10a+3a^2 | | 2(x-2)+x=3(x-5)+11 | | 4a^225=10a+3a^2 | | 2m-34=-4 | | 22x=23 |